PENGARUH MEDIA TANAM TERHADAP PERKECAMBAHAN BENIH KOPI ARABIKA (Coffea arabica L) - Yana Taryana; Lia Sugiarti (Jurnal AGROSAINS dan TEKNOLOGI, 2019)
A study to determine the effect of various types of mixed planting media on Arabica coffee seed germination was carried out in April to May 2019, located in the Experimental Garden of the Faculty of Agriculture, University of Winaya Mukti, Tanjungsari, Sumedang. This study used a randomized block design (RBD) consisting of 4 treatments and 5 replications. The planting media used in this study were mixed media consisting of A = soil; B = mixture of soil and manure (1: 1); C = mixture of soil and charcoal (1: 1); D = mixture of soil, manure and husk charcoal (1: 1: 1), The results of the study showed the planting media in the form of soil, a mixture of soil with manure or charcoal husk, and the mixture of the three did not affect the germination of seeds, but the use of in the form of a mixture of soil with manure and husk charcoal can increase the germination index compared to the media in the form of soil without mixture.